2010
DOI: 10.1007/s00535-010-0328-z
|View full text |Cite
|
Sign up to set email alerts
|

High ability to predict the treatment outcome of peginterferon and ribavirin combination therapy based on the reduction in HCV RNA levels at 4 weeks after starting therapy and amino acid substitutions in the hepatitis C virus in patients infected with HCV genotype 1b

Abstract: A ≥3 log(10) reduction in HCV RNA levels at 4 weeks after starting therapy indicates that a patient has a high likelihood of achieving an SVR as a final outcome. Additional information on the amino acid substitutions at residue 70 in the HCV core and within NS5A-ISDR will further increase the ability to predict a clinical response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…The percentage is comparable to that reported by Marcellin et al [5] and in our previous study [6]. Multivariate analysis indicated that factors associated with this failure include female sex, higher pretreatment HCV RNA levels, and lower baseline ALT activity.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The percentage is comparable to that reported by Marcellin et al [5] and in our previous study [6]. Multivariate analysis indicated that factors associated with this failure include female sex, higher pretreatment HCV RNA levels, and lower baseline ALT activity.…”
Section: Discussionsupporting
confidence: 78%
“…In addition to RVR, the degree of reduction in serum HCV RNA levels 4 weeks after starting therapy is useful; a 3.0 log 10 or more reduction in HCV RNA levels at 4 weeks indicates a high likelihood of achieving SVR even without RVR. Previous studies by Marcellin et al [5] and our group [6] showed that a ≥3.0 log 10 reduction at 4 weeks is associated with a high likelihood of both achieving a complete early virologic response (EVR), i.e. undetectable serum HCV RNA 12 weeks after starting therapy, and SVR.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several recent studies reported the predictive value of the degree of reduction in serum HCV RNA levels at 4 weeks after starting therapy [Yu et al, 2007;Huang et al, 2010;Toyoda et al, 2011]. Therefore, the viral dynamics of HCV at 4 as well as 12 weeks after starting therapy is important for response-guided therapy.…”
Section: Discussionmentioning
confidence: 95%
“…A rapid virologic response, in which serum HCV RNA is undetectable at 4 weeks after starting therapy, has been the strongest predictive factor of a sustained virologic response reportedly [Martinez-Bauer et al, 2006;Poordad et al, 2008;de Segadas-Soares et al, 2009;Martinot-Peignoux et al, 2009]. In addition, the predictive value of reduced serum HCV RNA levels at 4 weeks after starting therapy has been clarified further, and a !3 log 10 reduction in HCV RNA levels at 4 weeks after starting therapy has high predictive value that a patient will achieve a sustained virologic response as a final outcome, even in the absence of a rapid virologic response [Toyoda et al, 2011].…”
Section: Introductionmentioning
confidence: 99%
“…RVR was also significantly related to SVR in the previously relapsed group. Patients achieving RVR have a high likelihood of achieving SVR by PEG-IFN/RBV combination therapy [26,27]. Our study also suggested that achievement of RVR is essential for achieving SVR.…”
Section: Discussionmentioning
confidence: 48%